Effects of the Colored Pump Noise in a Two-Mode Laser - Youlin Xiang; Haiyun Lin; Jianchun Cai; Zucheng Dai; Yujiao Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
An inhomogeneously broadened two-mode ring laser system with the colored pump noise is considered. The effects of the auto-correlation time t of the colored pump noise on the competition between two modes in the laser system are investigated for the first time by the computer simulation method. The results show that when the laser system works far above threshold, the stationary properties of the laser intensities of two laser modes changes in quite other ways as the value of increases. It is obvious that the effects of the colored pump noise on the mode competition between two laser modes. Here does not exist mode competition for enough small value of t, it increases and then remain unchanged with increasing value of t. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3235